2016
DOI: 10.1044/2016_jslhr-s-15-0212
|View full text |Cite
|
Sign up to set email alerts
|

Initial Stop Voicing in Bilingual Children With Cochlear Implants and Their Typically Developing Peers With Normal Hearing

Abstract: Purpose: This study focuses on stop voicing differentiation in bilingual children with normal hearing (NH) and their bilingual peers with hearing loss who use cochlear implants (CIs). Method: Twenty-two bilingual children participated in our study (11 with NH, M age = 5;1 [years;months], and 11 with CIs, M hearing age = 5;1). The groups were matched on hearing age and a range of demographic variables. Single-word picture elicitation was used with word-initial singleton stop consonants. Repeated measures analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…As for specific speech patterns produced by young bilingual CI users, studies indicate that bilingual children who use CIs can match the productions of their bilingual peers with NH, such as in voice onset time and prevoicing in each language in word-initial position (Bunta, Goodin-Mayeda, Procter, & Hernandez, 2016). There are, however, unique patterns in the productions of bilingual and monolingual CI users that are reflected in differential productions of postalveolar fricatives and affricates showing effects of both bilingual versus monolingual status and CI use versus NH (Li, Bunta, & Tomblin, 2017).…”
Section: Speech Production In Bilingual Children Who Use Cismentioning
confidence: 99%
“…As for specific speech patterns produced by young bilingual CI users, studies indicate that bilingual children who use CIs can match the productions of their bilingual peers with NH, such as in voice onset time and prevoicing in each language in word-initial position (Bunta, Goodin-Mayeda, Procter, & Hernandez, 2016). There are, however, unique patterns in the productions of bilingual and monolingual CI users that are reflected in differential productions of postalveolar fricatives and affricates showing effects of both bilingual versus monolingual status and CI use versus NH (Li, Bunta, & Tomblin, 2017).…”
Section: Speech Production In Bilingual Children Who Use Cismentioning
confidence: 99%
“…Regarding the issue of establishing separate phonological representations for the alveolar and postalveolar obstruents in Spanish and English by bilingual children with CIs, a more complex and complete picture emerges than attested in previous work. Regarding initial stop consonants, Bunta, Goodin-Mayeda, et al (2016) found that, similar to bilingual children with NH, bilingual Spanishand English-speaking children with CIs not only differentiated voiced and voiceless stops in their target languages, but they did so differentially across those languages, suggesting language separation. In the present study, it became evident that bilingual children with CIs were able to distinguish fricatives and affricates in their productions of both English and Spanish.…”
Section: Discussionmentioning
confidence: 92%
“…Caldwell & Nittrouer, 2013;Giezen, Escudero, & Baker, 2010;Uchanski & Geers, 2003) or bilingual (cf. Bunta, Goodin-Mayeda, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations